Traditional Chinese Medicine for adjuvant treatment of breast cancer: Taohong Siwu Decoction - Huajuan Jiang; Minmin Li; Kequn Du; Chuan Ma; Yanfen Cheng; Shengju Wang; Xin Nie; Chaomei Fu; Yao He (BMC, 2021)
Abstract The high incidence of breast cancer is the greastest threat to women' health all over the world. Among them, HER-2 positive breast cancer has the characteristics of high malignancy, easy recurrence and metastasis, and poor prognosis. Traditional Chinese medicine (TCM) has a rich theoretical basis and clinical application for breast cancer. TCM believes that blood stasis syndrome is one of the important pathogenesis of breast formation and development. Taohong Siwu Decoction (TSHWD) is based on the "First Prescription of Gynecology" Siwu Decoction. It is widely used in various blood stasis and blood deficiency syndromes, mainly in gynecological blood stasis. Clinical studies have found that THSWD can treat breast cancer by reducing blood vessel and lymphangiogenesis with auxiliary chemotherapy. In this study, we aim to explore the material basis and mechanism of THSWD in the treatment of HER-2 positive breast cancer through literature review and network pharmacology studies. Through a literature review of the traditional application, chemical composition of Chinese herbal medicine of THSWD, as well as its clinical reports and pharmacological research on breast cancer treatment. Meanwhile, we conducted "component-pathway-target" network through network pharmacology reveals the main material basis, possible targets and pathways of THSWD in inhibiting HER-2 positive breast cancer. Literature review and network pharmacology research results had predicted that, baicalein, kaempferol, caffeic acid, amygdalin, quercetin, ferulic acid, gallic acid, catalpol, hydroxysafflor yellow A, paeoniflorin in THSWD are the main effective chemical composition. THSWD regulates 386 protein targets and 166 pathways related to breast cancer. The molecular mechanism is mainly to improve the microenvironment of tumor cells, regulate the process of tumor cell EMT, and inhibit tumor cell proliferation and metastasis. This study revealed the mechanism of action of THSWD in the treatment of HER-2 positive breast cancer through literature review and network pharmacology studies, providing a scientific basis for clinical application.